2006
DOI: 10.1097/01.blo.0000194682.33000.f9
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Comment

Abstract: Therapeutic study, Level III (Case control study). See the Guidelines for Authors for a complete description of levels of evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…A symmetrical distribution on funnel plot suggested no publication bias. There was a statistically significant increase in mortality among the geriatric population in 7 of the 12 studies [ 19 , 20 , 22 , 23 , 25 27 ], and a non-significant trend towards increased mortality in 4 of the remaining 5 [ 16 , 17 , 21 , 24 ]. One outlying study showed a non-significant trend towards decreased mortality in the geriatric population [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A symmetrical distribution on funnel plot suggested no publication bias. There was a statistically significant increase in mortality among the geriatric population in 7 of the 12 studies [ 19 , 20 , 22 , 23 , 25 27 ], and a non-significant trend towards increased mortality in 4 of the remaining 5 [ 16 , 17 , 21 , 24 ]. One outlying study showed a non-significant trend towards decreased mortality in the geriatric population [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies [ 17 , 21 , 23 , 24 , 28 32 ] reported deep vein thrombosis (DVT) as a complication after total knee arthroplasty (Fig. 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, Biau et al found no difference in cardiac, genitourinary, neuropsychiatric, thromboembolism, or decubitus ulcer in patients older than 85 years old and those less than 75 years old. 28 …”
Section: Discussionmentioning
confidence: 99%